Virulence diversity of Phakopsora pachyrhizi isolates from east Africa compared to a geographically diverse collection - Murithi, H.; Haudenshield, J.S.; Beed, Fenton D.; Mahuku, George S.; Joosten, M.H.; Hartman, G.L. (Scientific Societies, 2017)
Soybean rust, caused by the biotrophic pathogen Phakopsora pachyrhizi is a highly destructive disease that occurs in many soybean producing regions throughout the world causing substantial yield losses. Knowledge about P. pachyrhizi virulence is needed to guide development and deployment of soybean germplasm with durable resistance against all pathogen populations. To assess the virulence diversity of P. pachyrhizi, 25 isolates from eight different countries including 17 isolates from Africa were characterized on 11 soybean genotypes. All the isolates induced tan lesions with abundant sporulation on genotypes without any known resistance genes and on those with resistance genes Rpp4 and Rpp5b. The most durable gene was Rpp2 as 96% of the isolates induced reddish brown lesions with little or no sporulation. Of the African isolates tested, the South African isolate was the most virulent, whereas those from Kenya, Malawi and some of the isolates from Tanzania had the lowest virulence. An Argentinian isolate was virulent on most host differentials, including two cultivars carrying multiple resistance genes. Ten distinct pathotypes were identified in this study, four of which comprised the African isolates representing considerable P. pachyrhizi virulence. Soybean genotypes carrying Rpp1b, Rpp2, Rpp3, and Rpp5 resistance genes and cultivars Hyuuga and UG 5 were found to be resistant against most of the African isolates and therefore may be useful for soybean-breeding programs in Africa or elsewhere.